Atomically Dispersed Fe-Co Bimetallic Catalysts for the Promoted Electroreduction of Carbon Dioxide - Chen, Zhangsen; Zhang, Gaixia; Wen, Yuren; Chen, Ning; Chen, Weifeng; Regier, Tom; Dynes, James; Zheng, Yi; Sun, Shuhui (Nano-Micro Letters, 2021)
The electroreduction reaction of CO2 (ECO2RR) requires high-performance catalysts to convert CO2 into useful chemicals. Transition metal-based atomically dispersed catalysts are promising for the high selectivity and activity in ECO2RR. This work presents a series of atomically dispersed Co, Fe bimetallic catalysts by carbonizing the Fe-introduced Co-zeolitic-imidazolate-framework (C–Fe–Co–ZIF) for the syngas generation from ECO2RR. The synergistic effect of the bimetallic catalyst promotes CO production. Compared to the pure C–Co–ZIF, C–Fe–Co–ZIF facilitates CO production with a CO Faradaic efficiency (FE) boost of 10%, with optimal FECO of 51.9%, FEH2 of 42.4% at − 0.55 V, and CO current density of 8.0 mA cm−2 at − 0.7 V versus reversible hydrogen electrode (RHE). The H2/CO ratio is tunable from 0.8 to 4.2 in a wide potential window of − 0.35 to − 0.8 V versus RHE. The total FECO+H2 maintains as high as 93% over 10 h. The proper adding amount of Fe could increase the number of active sites and create mild distortions for the nanoscopic environments of Co and Fe, which is essential for the enhancement of the CO production in ECO2RR. The positive impacts of Cu–Co and Ni–Co bimetallic catalysts demonstrate the versatility and potential application of the bimetallic strategy for ECO2RR. Highlights: 1 X-ray photoelectron spectroscopy results confirmed the increased number of M–N sites in the bimetallic Fe–Co catalyst. 2 Synchrotron-based X-ray absorption fine structure demonstrated that the interaction in the coordination environments of the different transition metal sites facilitated the CO production in electroreduction reaction of CO2 (ECO2RR). 3 This bimetallic strategy has also been extended to fabricate other catalysts such as Cu–Co and Ni–Co, which also exhibited enhanced performance for ECO2RR.